2023
DOI: 10.1038/s41467-023-40401-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional divergence of CYP76AKs shapes the chemodiversity of abietane-type diterpenoids in genus Salvia

Abstract: The genus Salvia L. (Lamiaceae) comprises myriad distinct medicinal herbs, with terpenoids as one of their major active chemical groups. Abietane-type diterpenoids (ATDs), such as tanshinones and carnosic acids, are specific to Salvia and exhibit taxonomic chemical diversity among lineages. To elucidate how ATD chemical diversity evolved, we carried out large-scale metabolic and phylogenetic analyses of 71 Salvia species, combined with enzyme function, ancestral sequence and chemical trait reconstruction, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Protein expression was then induced with yeast extract peptone dextrose medium with 2% galactose for 16 hour at 28°C and 200 rpm. Then, the culture was immediately used for microsomal protein isolation following previous instructions ( 102 ). Enzyme reactions with CYP-enriched microsomal proteins were performed in tris-HCl buffer (pH 7.5) containing 5 μg of microsomal protein, 500 μM NADPH (reduced form of nicotinamide adenine dinucleotide phosphate), 50 μM senkyunolide A or ligustilide, and NADPH Regeneration System (Promega) in a total reaction volume of 200 μl.…”
Section: Methodsmentioning
confidence: 99%
“…Protein expression was then induced with yeast extract peptone dextrose medium with 2% galactose for 16 hour at 28°C and 200 rpm. Then, the culture was immediately used for microsomal protein isolation following previous instructions ( 102 ). Enzyme reactions with CYP-enriched microsomal proteins were performed in tris-HCl buffer (pH 7.5) containing 5 μg of microsomal protein, 500 μM NADPH (reduced form of nicotinamide adenine dinucleotide phosphate), 50 μM senkyunolide A or ligustilide, and NADPH Regeneration System (Promega) in a total reaction volume of 200 μl.…”
Section: Methodsmentioning
confidence: 99%
“…The products of the catalytic reaction and the extracts of the different plant species samples were analysed using an ACQUITY UPLC system coupled to a Xevo G2-XS QToF mass spectrometer (Waters), which was equipped with an electrospray ionization source. The conditions for the UPLC-Q-TOF/MS analysis were set as previously described (Hu et al, 2023). Mass-to-charge ratio (m/z) values are listed in Table S2.…”
Section: Metabolomic Profiling and Enzyme Catalytic Assays Analysismentioning
confidence: 99%
“…Gene duplication played an important role in the expanding of gene families in plant genomes [18,19,42]. It has been demonstrated that, multiple gene duplication events at the family level or above in campanulids, resulted in a large number of FAD2 homologs in Asterales and Apiales [7].…”
Section: Characteristics Of Fad2 Family Genes In Campanulidsmentioning
confidence: 99%
“…4, Table 1). After gene duplication, plants take up eliminating most redundant gene copies in a long evolutionary process generally, with some duplicated copies retained via neofunctionalizations, which is the cause of the occurrence of numerous specialized metabolites in some lineage-speci c plants [7,18,19,43]. Therefore, it can be concluded that gene duplication followed by functional diversi cation of FAD2 genes, giving rise to diverse PAs in campanulids.…”
Section: Characteristics Of Fad2 Family Genes In Campanulidsmentioning
confidence: 99%
See 1 more Smart Citation